2017
DOI: 10.1136/bmjopen-2017-017725
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy Diabetes Screening Trial: protocol for a pragmatic cluster-randomised controlled trial to compare three screening methods for undiagnosed type 2 diabetes in Australian community pharmacy

Abstract: IntroductionWith the rising prevalence of type 2 diabetes in Australia, screening and earlier diagnosis is needed to provide opportunities to intervene with evidence-based lifestyle and treatment options to reduce the individual, social and economic impact of the disease. The objectives of the Pharmacy Diabetes Screening Trial are to compare the clinical effectiveness and cost-effectiveness of three screening models for type 2 diabetes in a previously undiagnosed population.Methods and analysisThe Pharmacy Dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Since A1C only picked up 25.90% of undiagnosed diabetic adult participants diagnosed using FPG and/or 2hPG, substantial amount, 74.10%, of undiagnosed adult participants would be missed using A1C alone. Our observations are consistent with previous reports of low sensitivity of the current A1C cutoff [ 7 , 16 ]. Thus, it is a significant public health and clinical issue by missing diagnosis of diabetes exclusively based on A1C.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Since A1C only picked up 25.90% of undiagnosed diabetic adult participants diagnosed using FPG and/or 2hPG, substantial amount, 74.10%, of undiagnosed adult participants would be missed using A1C alone. Our observations are consistent with previous reports of low sensitivity of the current A1C cutoff [ 7 , 16 ]. Thus, it is a significant public health and clinical issue by missing diagnosis of diabetes exclusively based on A1C.…”
Section: Discussionsupporting
confidence: 93%
“…Despite ADA stating that DM may be diagnosed by FPG, 2hPG, and A1C with no preference [ 14 ], A1C has become widely used in various clinical and research settings, such as defining the prevalence of DM [ 15 , 16 ]. Although the low sensitivity of A1C in diagnosis of DM has been noted [ 8 ], the factors that may affect the performance of A1C in the diagnosis has not been well described.…”
Section: Introductionmentioning
confidence: 99%
“…Few experiences of pharmacy-based opportunistic screening for diabetes have been published in different countries such as Australia [14], Switzerland [15], Spain [16,17], each of them based on different questionnaires and scorecards. All of them reported that pharmacies, also thanks to their high accessibility, are an appropriate setting for screening for diabetes, as well as for other risk factors for cardiovascular diseases [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Some recent evidence suggests that using POC A1c analyzers for diabetes screening in primary care clinics may increase identification of prediabetes and diabetes compared to usual care [50]. Expansion of POC devices for diabetes screening in dental offices, pharmacies, and community-based settings are promising, but require clear instructions about follow-up procedures and linkage to clinical care for those who require repeat testing or treatment [51,52]. The endorsement of ambulatory blood pressure measurement in the USPSTF hypertension screening guideline suggests the potential for a similar community-based approach in diabetes screening [53•, 54].…”
Section: Current Gaps and Ongoing/future Work: New Opportunities For mentioning
confidence: 99%